ANALISIS PERHITUNGAN SISTEM PERPIPAAN HYDRANT PILLAR DAN SPRINKLER PADA LANTAI I GEDUNG SIMULATOR SEKOLAH TINGGI PENERBANGAN INDONESIA - Viyan Fajrian; KGS. M. Ismail; Andri Kurniawan (Langit Biru: Jurnal Ilmiah Aviasi, 2018)
Fire is a disaster that caused by undesireble fire also could cause a big loss both of property or human life as well. therefore, the prevention system of fire is the most important thing. In the simulator building of Indonesia Civil Aviation Institute, there is only a hydrant pillar pipe that has no water supply, fire pump and sprinkler as the first prevention of fire hazard. therefore this issue is in the analysis The calculation analysis is done by determining the location of sprinkler, calculating the capacity of the water , and determining the power of the pump with counting the total of head loss on that pump. Refering to SNI 03-3989-2000, SNI 03- 1457-2000, related articles, last finally project and theories on plumbing system also using ANSYS 16.0 for helping the counting analysis. The result of calculation analysis is location of sprinkler, water volume and pump force to instalation hydrant and sprinkler for prevention hazard.